PENGGUNAAN MODEL PEMBELAJARAN CONTEXTUAL THEACING LEARNING (CTL) UNTUK MENINGKATKAN KETERAMPILAN BELAJAR MATERI BERWUDHU KELAS I SDN KALIANGET BARAT III KABUPATEN SUMENEP - Sutrisno, Tri (Rabbani: Jurnal Pendidikan Agama Islam, 2022)
Abstract This research activity procedurally uses the Classroom Action Research (CAR) design. The results of the study, the use of the Contextual Theacing Learning (CTL) learning model can improve learning skills about ablution in grade 1 students of SDN Kalianget Barat III Sumenep Regency. This can be seen in the increase in the average value of learning skills in cycle I and cycle II, namely cycle-1 70.1 and cycle-2 89.96, it is seen that almost all students are skilled in performing ablution movements. This means that learning with the Contextual Theacing Learning (CTL) method can improve learning skills.